Nonlinear dynamical processes in musical interactions: Investigating the role of nonlinear dynamics in supporting surprise and exploration in interactions with digital musical instruments. Issue 128 (August 2019) - Mudd, Tom; Holland, Simon; Mulholland, Paul
Highlights: Nonlinear dynamical processes play a significant role in instrumental interactions. Nonlinear dynamical processes can support deep exploration in digital interactions. Interactions with nonlinear dynamical processes can be learnable and controllable. Nonlinear dynamical processes offer potential for new creative digital technologies. Abstract: Nonlinear dynamical processes play a central role in many acoustic instruments, yet they rarely feature in digital instruments, and are little understood from an interaction design perspective. Such processes exhibit behaviours that are complex, time-dependent, and chaotic, yet in the context of acoustic instruments can facilitate interactions that are explorable, learnable and repeatable. This suggests that these processes merit deeper investigation for digital music interaction design. Two studies are presented which investigate user interaction with nonlinear dynamical musical tools. A lab-based study used four purpose-built digital musical instruments to test interaction designs featuring nonlinear dynamical processes. Evaluations with 28 musicians demonstrated the potential for these processes to provoke creative surprises, and support exploration without a corresponding loss of control. A subsequent ethnographically-informed study with 24 musicians linked these findings to a mode of engagement which we term 'edge-like interaction'. Edge-like interactions draw on the complex, unpredictable behaviours found in nonlinear dynamical processes close to critical thresholds, facilitating creative exploration. The two complementary studies provide evidence both for the existing importance of nonlinear dynamical processes in musical interactions with acoustic interactions, and their potential for deployment in the development of new creative digital technologies, musical or otherwise.